Effect of Transcatheter Arterial Chemoembolization Combined with Radiofrequency Ablation on Liver Function and Immune Function in Patients with Hepatocellular Carcinoma - Yan Zhou; Ying Qian; Weiming Xiong; Naijun Yan; Bing Hu; Zhiyuan Xiong; Weixin He (Emergency Medicine International)
Objectives. To investigate the effects of transcatheter arterial chemoembolization (TACE) combined with radiofrequency ablation (RFA) on liver function and immune function in patients with hepatocellular carcinoma (HCC). Methods. From December 2016 to January 2019, patients with primary liver cancer who could not be operated on were selected as the study subjects. 170 patients were randomly divided into two groups. The control group was treated with transcatheter arterial chemoembolization (n = 85). The patients in the observation group were treated with transcatheter arterial chemoembolization combined with radiofrequency ablation (n = 85). The clinical effects of the two groups were analyzed. The changes of liver function and immune function were detected by automatic biochemical analyzer before and after treatment. The changes of hypoxia inducible factor-1 (HIF1) alpha and vascular endothelial growth factor (VEGF) levels before and after treatment were analyzed by enzyme-linked immunosorbent assay (ELISA). Results. The total effective rate in the observation group was significantly higher than that in the control group (P<0.05). After treatment, serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), CD8+, HIF1 alpha, and VEGF decreased significantly (P<0.05), while levels of total bilirubin, direct bilirubin, indirect bilirubin, CD3+, CD4+, and CD4+/CD8+ increased significantly (P<0.05). The changes of the above indexes in the observation group were more significant than those in the control group (P<0.05). Conclusion. Hepatic arterial chemoembolization combined with radiofrequency ablation has a significant effect on liver function and immune function in patients with liver cancer, which may be related to the abnormal levels of HIF1α and vascular endothelial growth factor.